Role of Plasmapheresis in the Treatment of Severe Pruritus in Pregnant Patients with Primary Biliary Cirrhosis: Case Reports. (2008) - Alallam, Alallam; Barth, David; Heathcote, E Jenny
Abstract : BACKGROUND: Primary biliary cirrhosis (PBC) may be associated with pruritus and, when present, may be accentuated during pregnancy. Several therapeutic modalities have been used to control itching caused by cholestasis, with variable responses. Drug therapies are ill-advised, particularly in early pregnancy. Plasmapheresis has been successful in controlling pruritus in patients with cholestasis. The use of plasmapheresis to alleviate severe life-threatening pruritus during pregnancy is reported in two patients with PBC. CASE PRESENTATIONS: Two patients with PBC presented during their second trimester of pregnancy with severe pruritus that did not respond to the anion exchange resin cholestyramine. Their symptoms were disabling to the point that one patient had suicidal ideation. Given the severity of their symptoms, multiple sessions of plasmapheresis were instituted with good control of pruritus. Both patients tolerated the procedure well and delivered healthy babies. CONCLUSION: Plasmapheresis is a relatively safe and rapidly effective treatment for severe pruritus during pregnancy in patients with PBC.